Hubungan Antara Self-Compassion dengan Resiliensi Akademik pada Siswa Kelas XI di SMA Negeri 1 Depok Sleman - Rahmawati, Septiana; Syah, Muhammad Erwan (SENTRI: Jurnal Riset Ilmiah, 2026)
High school students face various academic demands—such as assignments, exams, performance-based competition, and expectations from both school and family—that can generate academic pressure. Navigating these conditions requires the ability to endure, adapt, and bounce back from adversity, a quality known as academic resilience. One internal factor believed to play a role in enhancing academic resilience is self-compassion: an individual's ability to treat themselves with kindness, recognize failure as a part of the human experience, and maintain a balanced awareness of negative experiences. This study aimed to examine the relationship between self-compassion and academic resilience among 11th-grade students at SMA Negeri 1 Depok Sleman. A quantitative approach utilizing a correlational method was employed. The study involved 146 11th-grade students from SMA Negeri 1 Depok Sleman, selected via random sampling. Data were collected using a modified Self-Compassion Scale (based on Neff’s theory) and a modified Academic Resilience Scale-30 (ARS-30; based on Cassidy’s theory). The data were analyzed using the Pearson correlation technique. The results revealed a correlation coefficient of 0.797 with a significance value of 0.000 (p < 0.05), indicating a strong relationship; thus, the research hypothesis was accepted. Categorization results showed that the majority of students possessed moderate to high levels of both self-compassion and academic resilience. Consequently, it can be concluded that there is a significant positive relationship between self-compassion and academic resilience: higher levels of self-compassion correspond to higher levels of academic resilience, and vice versa. These findings have implications for the development of guidance and counseling programs that focus on fostering self-compassion as a means to strengthen students' academic resilience.